Radio-frequency connectors. RF coaxial connectors with inner diameter of outer conductor 6, 5 mm (0, 256 in) with bayonet lock. Characteristic impedance 50 ohms (Type BNC). (15th January 1997) - British Standards Institution,
No abstract available